Structural Analysis of Pedagogic Mediation in a Foreign Language Classroom - Nora Kats; Anna Rubtsova; Daria Bylieva (MDPI AG, 2024)
Cultural diffusion and a paradigm shift from a "skill-based" approach to an "action-oriented" approach in language pedagogy transform the functions of an educator in a foreign language classroom. A language instructor accepts an intermediatory role in learners' interactions with the environment, using language as a primary mediation tool. Thus, by being involved in varied social contexts and activities, a language educator mediates learning, communication, and sociocultural environments. This study relies on a structural analysis to investigate the mediating role of a language educator. It suggests that pedagogic mediation should be viewed as a specific form of language educators' activity and described through three dimensions: mediating learning, mediating communication, and mediating sociocultural space. In the teaching and learning context, these dimensions manifest themselves as skills to adapt to the instructional and linguistic complexity of texts, manage interaction, facilitate communication in sensitive situations, etc. Drawing upon a phenomenological research design and qualitative methods, the study develops illustrative descriptors that can be used in a foreign language classroom to assess the patterns of social, instructional, and communicative behavior of educators. The developed descriptors allowed for exploring the self-perceptions of pre-service language teachers towards their abilities for pedagogic mediation in a foreign language classroom. The results of the study identified the learning gaps among novice language teachers that can be further addressed as learning objectives while designing a curriculum for professional training in language education.